Criterion validity of the D-KEFS color–word and verbal fluency switching paradigms following traumatic brain injury. Issue 9 (21st October 2017) - Anderson, Luke B.; Jaroh, Rebekah; Smith, Hillary; Strong, Carrie-Ann H.; Donders, Jacobus
ABSTRACT: The present study was composed of two parts examining the clinical utility of the Delis–Kaplan Executive Function System (D-KEFS) Verbal Fluency and Color–Word subtests in traumatic brain injury (TBI). In the first part, the performance of 128 outpatients with mild to severe TBI on the Verbal Fluency and Color–Word subtests was examined in relation to two primary indicators of TBI severity: length of coma and the presence of intracranial lesions on neuroimaging through regression analysis. After controlling for education, ethnicity, and complicating premorbid and comorbid factors, length of coma predicted performance on the Color–Word Inhibition/Switching subtest, whereas the presence of diffuse lesions was related to Verbal Fluency Category Switching performance. In the second part of this study, performance on the Category Switching and Inhibition/Switching subtests was compared between a group of 28 participants with moderate-to-severe TBI and demographically matched groups with mild-uncomplicated TBI ( n = 28) and neurologically healthy control participants ( n = 56). The moderate-to-severe TBI group performed significantly worse on both subtests than the mild-uncomplicated TBI and control groups, and the latter groups did not differ from each other on these subtests. Logistic regression analysis showed that the combined group classification accuracy of these subtests was 66.07%, with an area under the curve (AUC) of .70 and a likelihood ratio of 1.93. The findings provide modest support for the clinical utility of the Color–Word Inhibition/Switching subtest in the cognitive assessment of TBI, while also replicating prior research suggesting clinical utility of the Category Switching subtest in this population.